2007
DOI: 10.1029/2007gl030377
|View full text |Cite
|
Sign up to set email alerts
|

Radiative forcing of black carbon over eastern India

Abstract: [1] Measurements of aerosol Black Carbon using a 7 channel Aethalometer at Visakhapatnam, a coastal tropical station on the east coast of India are used to study the temporal variation of surface BC mass concentration. The surface BC mass concentrations show a significant diurnal variation which is seasonally dependant. Analysis using the multi spectral data indicates that the BC mass does not show significant absorption due to non-BC aerosol species which indicates that the surface BC mass is dominated by fos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
54
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(64 citation statements)
references
References 18 publications
(22 reference statements)
8
54
0
2
Order By: Relevance
“…Further, the nocturnal boundary layer (NBL) is shallower than its day time counter part by a factor of about 3 (Kunhikrishnan et al, 1993). Also, the reduced ventilation coefficient due to lower wind speed at night leads to confinement of aerosol and consequently an increase in its concentration during early night (Sreekanth et al, 2007). As the night progresses, the decrease in local anthropogenic activities and traffic emission results in a reduction in basic generation and consequently EBC concentration decreases.…”
Section: Diurnal Variationmentioning
confidence: 99%
“…Further, the nocturnal boundary layer (NBL) is shallower than its day time counter part by a factor of about 3 (Kunhikrishnan et al, 1993). Also, the reduced ventilation coefficient due to lower wind speed at night leads to confinement of aerosol and consequently an increase in its concentration during early night (Sreekanth et al, 2007). As the night progresses, the decrease in local anthropogenic activities and traffic emission results in a reduction in basic generation and consequently EBC concentration decreases.…”
Section: Diurnal Variationmentioning
confidence: 99%
“…The seasonal changes in heating rate resemble that of seasonal variations in AOD indicates their strong affinity. , Babu et al (2007), Sreekanth et al (2007), and Dey and Tripathi (2008) have reported heating rate over Ahmedabad, Trivandrum, Visakhapatnam, and Kanpur to be 0.6Á1.13, 0.62Á1.51, 0.09Á1.23 and Â1 K/day respectively, for different seasons. The seasonal heating rate differs from place to place depending on abundance of aerosols, seasons, location, underlying surface, and so on.…”
Section: Comparison and Implications To Regional Climatementioning
confidence: 99%
“…In recent years, many studies have been undertaken to assess the impact of aerosols on the climate in the Indian region Ramanathan et al, 2001b;Moorthy et al, 2005;Ramachandran, 2005aRamachandran, , 2005bTripathi et al, 2005;Pant et al, 2006;Niranjan et al, 2007;Babu et al, 2007;Sreekanth et al, 2007;Dey and Tripathi, 2008). However, a few long-term (5-yr or so) studies have been carried out, whereas most of the other studies are limited in observations span.…”
Section: Introductionmentioning
confidence: 99%
“…Biomass burning for agricultural purposes and domestic purposes from the Indo-Gangetic Plain regions has been reported to be the major source for BC emissions (Venkatraman et al, 2005). However, there are very few data available on BC aerosols from the Indian region though some studies (Latha and Badarinath, 2003;Latha et al, 2004;Tripathi et al, 2005;Ramachandran and Rajesh, 2007;Safai et al, 2007;Sreekanth et al, 2007) have reported on the characteristics of BC over the Indian region.…”
Section: Introductionmentioning
confidence: 99%